2007
DOI: 10.1103/physrevlett.99.226106
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Mediated Patterning of Surfactant-Coated Nanoparticles and Surfaces

Abstract: We perform atomistic and mesoscale simulations to explain the origin of experimentally observed stripelike patterns formed by immiscible ligands coadsorbed on the surfaces of gold and silver nanoparticles. We show that when the conformational entropy gained via this morphology is sufficient, microphase-separated stripelike patterns form. When the entropic gain is not sufficient, we instead predict bulk phase-separated Janus particles. We also show corroborating experimental results that confirm our simulationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
377
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(420 citation statements)
references
References 31 publications
37
377
6
Order By: Relevance
“…It is known that most mixtures of thiolated molecules when coassembled on flat gold surfaces phase-separate into randomly sized and arranged domains (11,12). Recently (13)(14)(15)(16)(17)(18)(19), using scanning tunneling microscopy (STM) and infrared spectroscopy, we found that when gold nanoparticles are coated with these same types of binary mixtures of molecules, phase separation occurs in a more ordered fashion, leading to the formation of ribbonlike domains of alternating composition with an unprecedented small average domain width of ϳ5 Å (see cartoon in Fig. 1).…”
mentioning
confidence: 99%
“…It is known that most mixtures of thiolated molecules when coassembled on flat gold surfaces phase-separate into randomly sized and arranged domains (11,12). Recently (13)(14)(15)(16)(17)(18)(19), using scanning tunneling microscopy (STM) and infrared spectroscopy, we found that when gold nanoparticles are coated with these same types of binary mixtures of molecules, phase separation occurs in a more ordered fashion, leading to the formation of ribbonlike domains of alternating composition with an unprecedented small average domain width of ϳ5 Å (see cartoon in Fig. 1).…”
mentioning
confidence: 99%
“…23 Thus, computational approaches may help identifying driving forces to guide the design of new dissymetric, Janus or patchy nanoparticles by the rational choice of reagents and synthesis conditions. Coarse-grain molecular dynamics (MD), [24][25][26][27] Atomistic MD, 28 and Monte Carlo simulations, 28 have identified conformational entropic effects as the driving force for nanophase separation in binary thiol SAMs on gold nanoparticles, provided that the two kinds of molecules are not miscible and have sufficiently different chain lengths. 24,[27][28] Similar conclusions were reached for ternary and quaternary thiol SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…Coarse-grain molecular dynamics (MD), [24][25][26][27] Atomistic MD, 28 and Monte Carlo simulations, 28 have identified conformational entropic effects as the driving force for nanophase separation in binary thiol SAMs on gold nanoparticles, provided that the two kinds of molecules are not miscible and have sufficiently different chain lengths. 24,[27][28] Similar conclusions were reached for ternary and quaternary thiol SAMs. [25][26]29 However, the role of specific inter-chain interactions on phase segregation has been mostly eluded in simulations, except in very recent reports based on discrete MD simulations, where tail-tail repulsive interactions have been suggested to contribute to nanophase segregations for some specific ligand types.…”
Section: Introductionmentioning
confidence: 99%
“…However, the NR profile can detect the presence of domains like those formed in amphiphilic Janus NPs, where each domain is preferentially immersed in one of the two media and the domain boundary is parallel to the interface. This Janus morphology can be obtained during the synthesis and it is driven by the interplay of enthalpic and entropic effects 39 as well as kinetic effects. 45,46 To test the possible existence of Janus NPs in our monolayers, we modeled the NPs with Janus nanodomain structure (see ESI †) and fitted the experimental data to this model.…”
Section: Mixed Ligand Nps (D-ot : Mhol 1 : 1)mentioning
confidence: 99%
“…[36][37][38] Among these arrangements, Janus (two different sides), narrow nanodomains (stripes) and uniformly mixed morphologies have been reported in experimental and theoretical papers. [39][40][41] The size of NPs, chemical nature of the ligands and their arrangement at the surface affect their interaction with interfaces and therefore their use in different applications.…”
Section: Introductionmentioning
confidence: 99%